Treatment of localized gingival recessions using enamel matrix derivative as an adjunct to laterally sliding flap: 2 case reports - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2009)
Predictable and optimal coverage of exposed root surfaces is an important goal in periodontal plastic surgery. In this report, recession coverage was performed as laterally sliding flap technique with the adjunctive use of enamel matrix derivative (EMD). The cases of 2 female patients with gingival recession on the maxillary canines are presented with 1-year follow-up observation. Initial vertical gingival recessions were 4.0 mm each, with a probing depth of 1.0 mm. The surgical procedure immediately produced a marked reduction in gingival recessions. In the course of healing, the soft tissue margin on the operated teeth showed some shrinkage in the first months. After 1 year, complete root coverage (100%) was observed, with a probing depth of 0.5 mm and 5.0-mm gain of clinical attachment in both cases, and there was 0.5-mm creeping tissue above the cemento-enamel junction. Within the limits of these cases, the results demonstrated the possibility of treating human buccal recessions with EMD plus laterally sliding flap, with predictable root coverage and clinical attachment gain. (Quintessence Int 2009; 40: 461-469)
Keywords: bioengineering; enamel matrix protein derivative; gingival recession; laterally sliding flap; mucogingival surgery; root coverage; GUIDED TISSUE REGENERATION; CORONALLY ADVANCED FLAP; CONNECTIVE-TISSUE; PERIODONTAL REGENERATION; ROOT COVERAGE; HISTOLOGIC EVALUATION; CREEPING ATTACHMENT; PROTEINS; DEFECTS; EMDOGAIN